Dots and Acute Accent Shapes in the Dobrejšo Gospel - Vakareliyska, Cynthia M. (Studia Ceranea, 2016)
This paper examines the distribution of three types of sporadic and infrequent diacritics in the Dobrejšo Gospel and their functions: a dot or acute-accent shape over a liquid consonant letter in OCS trъt/trьt formations, and, more rarely, over other consonant letters in clusters; a single or multiple acute-accent shape over the letter л or н in certain words; and a titlo over unabbreviated words containing OCS trъt/trьt formations.